DIGITAL LITERACY IN EFL TEACHING - Hamidah, Nuriyatul (Institut Agama Islam Negeri Ponorogo, 2021)
Many questions have aroused in terms of media and technology used and its implication for language teaching and learning. The focus is on how students can be critically aware of media, especially digital media, for their learning. Thus, the use of media in education impacts educational creativity development, such as digital technology applications. In terms of learning, digital literacy is the competency in understanding and using digital technologies effectively for learning. Research has already explored the need for digital literacy in the classroom. This recent paper tries to figure out how digital literacy is implemented in the teaching of ESP students. Furthermore, the method used to describe the idea of this paper is a conceptual paper in which the writer tries to figure out how digital learning is implemented for learning. The writer used literature review from some journal articles and books written by the experts to gather the data. In conclusion, applying digital literacy must be well prepared on the way how it is used. It must relate to their competence, learning objectives, and language skills being taught. Indeed, once the students are familiar with the technology being used, they significantly improve their skills.